2009
DOI: 10.1002/clen.200700208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visitor Activities on Surface Soil Environmental Conditions and Aboveground Herbaceous Biomass in Ayder Natural Park

Abstract: The effects of visitor activities on surface soil environmental conditions and aboveground herbaceous biomass in Ayder Natural Park, Turkey, were investigated. Soil properties and aboveground herbaceous biomass were identified and characterized as heavily trafficked site (HTS), moderately trafficked sites (MTS) and control (non-trafficked site) in grassland in a forest gap. Some soil properties were measured on 60 pits at 0 -5 and 5 -10 cm soil depths. The intensity of visitor activities had a negative impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
1
6
0
4
Order By: Relevance
“…RG soils had higher bulk densities than cultivated soils, possibly due in part to trampling when the alfalfa was mown manually by local farmers. This is in agreement with previous study that showed heavy pedestrian traffic can have a negative impact on surface soil properties [31]. Cropland soils had lower bulk densities, mainly presumably because of tillage management ( p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…RG soils had higher bulk densities than cultivated soils, possibly due in part to trampling when the alfalfa was mown manually by local farmers. This is in agreement with previous study that showed heavy pedestrian traffic can have a negative impact on surface soil properties [31]. Cropland soils had lower bulk densities, mainly presumably because of tillage management ( p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…The significant increase in bulk density ( D b ) and SPR, and significant decrease in total porosity and SOM possibly affected FC, PWP and PAW values (see Table II). Froehlich and McNabb (1983) and Yüksek (2009) reported that soil compaction has a variable effect on water characteristic of soils.…”
Section: Resultsmentioning
confidence: 99%
“…High ρ s under the cultivated treatment was attributed to the high-frequency of trampling occasioned by human activities [11,51]. Especially during the harvest season, an escalated use of agricultural machinery as well as regular human activities contributed to even greater soil compaction, further increasing ρ s [51,54]. Under the abandoned treatment, the higher ρ s may be attributable to a lack of extensive strong roots [6,52].…”
Section: Effects Of the Stand Type On ρ S And Phmentioning
confidence: 99%
“…However, the current study found that the mean ρ s under the 16-year-old apricot treatment was significantly lower than that under the 40-year-old treatment (Figure 3). This was likely related to: (1) the reduction of AGB and SD with increasing apricot stand age (Table 2) [52,53]; (2) greater compaction under the 40-year-old treatment [54]; and (3) root growth under the 16-year-old apricot treatment loosening the soils, whereas, after 40 years, apricot root growth had slowed or stopped, reducing their loosening effect on the soil. Soil pH also varied significantly with stand age.…”
Section: Effects Of the Stand Age On ρ S And Phmentioning
confidence: 99%